2016
DOI: 10.1101/048124
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The contribution of alternative splicing probability to the coding expansion of the genome

Abstract: Alternative splicing results in the inclusion or exclusion of exons in an RNA, thereby allowing a single gene to code for multiple RNA isoforms. Genes are often composed of many exons, allowing combinatorial choice to significantly expand the coding potential of the genome. How much coding potential is gained by alternative splicing and what is the main contributor: alternative-splicing-depth or exon-count? Here we develop a splice-site-centric quantification method, allowing us to characterize transcriptome-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In eukaryotes pre-mRNA processing is key to gene regulation and the generation of isoform diversity. Alternative splicing is arguably the most pivotal mRNA processing mechanism in higher eukaryotes, and in humans it contributes substantially to the protein diversity, affecting 95% of mRNA transcripts (Pan et al 2008), , (Licatalosi & Darnell 2010;Oesterreich et al 2016). Moreover, alternative splicing is essential for normal cell growth, cell death, differentiation, development, sex, circadian rhythms, responses to environmental changes and pathogen responses (Bell et al 1988), (Kalsotra & Cooper 2011), (Irimia & Blencowe 2012).…”
mentioning
confidence: 99%
“…In eukaryotes pre-mRNA processing is key to gene regulation and the generation of isoform diversity. Alternative splicing is arguably the most pivotal mRNA processing mechanism in higher eukaryotes, and in humans it contributes substantially to the protein diversity, affecting 95% of mRNA transcripts (Pan et al 2008), , (Licatalosi & Darnell 2010;Oesterreich et al 2016). Moreover, alternative splicing is essential for normal cell growth, cell death, differentiation, development, sex, circadian rhythms, responses to environmental changes and pathogen responses (Bell et al 1988), (Kalsotra & Cooper 2011), (Irimia & Blencowe 2012).…”
mentioning
confidence: 99%
“…Compared to these simple types of splicing events, complex events involve multiple alternative splice sites or exons and according to Vaquero-Garcia et al (2016) constitute at least one-third of AS events observed in human and mouse tissues. Methods such as JUM ( Wang and Rio, 2018 ), MAJIQ ( Vaquero-Garcia et al , 2016 ) and the method proposed in Oesterreich et al (2016) , therefore consider AS units that generalize simple events to more complex patterns. They quantify the relative usage of an arbitrary number of introns that share a common splice site.…”
Section: Introductionmentioning
confidence: 99%
“…Complex events, on the other hand, involve multiple alternative splice sites or exons and according to [48] constitute at least one-third of AS events observed in human and mouse tissues. Methods such as JUM [52], MAJIQ [48] and the splice-site-centric quantification method proposed in [33], therefore consider AS units that generalize simple events to more complex patterns. They quantify the relative usage of an arbitrary number of introns that share a common splice site, such as the three introns sharing common donor site s 1 in Fig.…”
Section: Introductionmentioning
confidence: 99%